The sensitivity of some species of entomoacarifages to the insectocaricides used in the protection of apple culture - Batco, M.; Sumencova, V.; Iordosopol, E. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
The apple orchard populations of acariphagous (Stethorus punctillum Weise, Chrysopa carnea Steph, and mite-predators Amblyseius andersoni Chan, Metaseilus occidentalis Nesbit and Neoseiulus californicus Mc Gregor), which were at least 25 years under pesticide treatment, were studied. Our studies show that for these populations the least toxic pesticide is Avaunt, EC, Talstar 10 EC, Omite 30 WP, Confidor 200 SL and the most toxic pesticide is Vertimec 018 EC, Dursban 480 EC for both entomophagous. BI-58 New is slightly toxic for the larvae of C. carnea and highly toxic for N. californicus in laboratory culture. The orchard populations of acariphagous develop resistance to BI-58 New, Dursban 480 EC and Decis f-Luxx 025 EC, in the conditions of the prolong pesticide treatment. The discovery of natural populations of entomophagous resistant to pesticides is of high importance due to its potential practical use.